Atos de criação: as origens culturais da brincadeira dos bebês - Elenice de Brito Teixeira Silva (2021)
In a context of institutionalization of the right to play in Early Childhood Education, what are the relationships and principles that enable the constitution of play as an activity for infants and children? What generates the social need to play in a group that shares the collective context of care and education? What dialectical transformations happen in the cultural development of infants, in spaces/times, in social relations and in play? From the study on the processes of constitution of play in a group of infants over a two-year period in Early Childhood Education (2017-2018), we argue that it is the need for participating in the group that mobilizes intentions, actions, mastery and appropriation of social practices, languages and the shared activity that allows for the emergence of play. The social events that affect the lives of infants and children, inside and outside the school, circumscribe the cultural content of the imaginary situations created in the interactions with peers, teachers, support professionals and cultural artifacts. The historicity of these cultural contents of play — space, time, collective cultural routines and care routines — supports the arguments for the thesis that the play of infants and children is an act of creating possibilities of participation in the social group and of creating meanings for the events of collective life; an act constituted by the unity [action/imagination], which expands the capability to act, communicate, relate, affect, be affected and share intentions, symbols and meanings with Others. The field research was carried out at a Municipal School of Early Childhood Education in Belo Horizonte (EMEI Tupi) — Minas Gerais, Brazil — based on the ontological and epistemological foundations of Historical-Cultural Theory and Ethnography in Education, as well as on dialogues with Infant and Child Studies. The epistemology for understanding the production of the existence of infants in collective contexts and the constitution of singularities is based on the ontology of infants as potente and vulnerable social beings who, in their relationships with Others and with materialities, produce subjectivities, individualities and human singularity. Therefore, understanding the constitution of play discloses the political and social status of collective care and education practices. All the empirical material was generated through observations of the group’s daily life, registered with video recording resources, photographs and a field diary, through a logic of dialectic-abductive research. The processes of constituting singing games and role-playing mother and daughter in the group’s trajectory show their cultural genesis, their concreteness in collective social practices and in relationships of otherness built through the sharing of narrative and symbolic sources, cultural and care routines at EMEI Tupi. The analyses allow us to affirm that there is the creation of imaginary situations through the languages in use and, in these situations, there is the creation of expressiveness, communicability, repercussions, surprises, uses of objects as representative gestures that are keys of the symbolic function, of a social system of speech in which one has what, where and to whom to speak. The visual symbols created are experienced in [action/imagination] in a particular way and become part of the group, which makes it possible to institute emerging alterity and collectivity. This creative principle of an exercise in the humanization of the world by infants and children has ethical, aesthetic and political meanings for Pedagogies aligned with the defense of the right to play and the production of subjectivities, and a resistance movement in the face of the standardization processes since Early Childhood Education.